2018
DOI: 10.1016/j.clim.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

What have we learned from BeSt?

Abstract: Early treatment determines early clinical improvement, treatment-to-target determines long term outcomes. Prevention of relevant radiologic damage progression and disability, drug free remission and normalized survival are realistic goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Of the 3879 articles identified through the literature search, 66 articles were selected after title, abstract, full-text and reference screening (figure 1). 27–92 Characteristics of selected articles including RoB assessments are shown in online supplemental table S1. These 66 selected articles concerned results from 40 studies, and from these the data of 169 treatment arms were extracted.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 3879 articles identified through the literature search, 66 articles were selected after title, abstract, full-text and reference screening (figure 1). 27–92 Characteristics of selected articles including RoB assessments are shown in online supplemental table S1. These 66 selected articles concerned results from 40 studies, and from these the data of 169 treatment arms were extracted.…”
Section: Resultsmentioning
confidence: 99%
“…A PRISMA flow diagram for our systematic review is shown in Figure 1 and includes the number of citations found and screened. We identified six RCTs (reported in 26 full text publications) of first-line infliximab in RA: ASPIRE (3 publications) [15,32,33], BeSt (15 publications) [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], Durez 2007 (1 publication) [49], IDEA (1 publication) [12], NEO-RACo (3 publication) [50][51][52] and Quinn 2005 (3 publications) [53][54][55]. The sample size of these RCTs ranged from 20 to 1,049 patients; follow-up times were between 1 and 10 years.…”
Section: Literature Search Of Clinical Studiesmentioning
confidence: 99%